(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This topic will cover modern diagnostic and therapeutic methods used in the field of thoracic oncology. The importance of low-dose computed tomography (LDCT), PET/CT, molecular genetic tests, and biomarkers in the early detection of tumors of the lungs, mediastinum, and chest organs will be reviewed. Innovative approaches to treatment, such as minimally invasive surgery (VATS, robot-assisted), precisely targeted radiation therapy (IMRT, SBRT), targeted therapy, and immunotherapy, will be analyzed. The role of a multidisciplinary approach in choosing an individual treatment strategy will also be emphasized. Modern technologies are helping to improve the survival and quality of life of patients.